2020
DOI: 10.32734/ijnpc.v2i02.3910
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ginkgo Biloba Against Ototoxic Hearing Loss on Advanced Stage Undifferentiated Nasopharyngeal Carcinoma Receiving Cisplatin Chemotherapy

Abstract: Introduction: Undifferentiated nasopharyngeal carcinoma is the most common malignant tumor in nasopharynx, in which most patients come to a hospital in advanced stage. Cisplatin is one of the most effective widely used chemotherapy drugs for advanced stage undifferentiated nasopharyngeal carcinoma. Although it provides a successful outcome against cancer, there is serious side effect namely ototoxic hearing loss. Ginkgo biloba is a powerful antioxidant which may prevent ototoxic hearing loss. Objective: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…One study failed to demonstrate a significant benefit for GB in preventing ototoxicity as defined by the ASHA criteria. 1 However, in another study that used higher doses of the intervention, GB was associated with significantly higher signal amplitudes and S/N ratio at 8,000 Hz. 11 The same study also reported no adverse events and no significant interference with the antitumor activity of cisplatin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One study failed to demonstrate a significant benefit for GB in preventing ototoxicity as defined by the ASHA criteria. 1 However, in another study that used higher doses of the intervention, GB was associated with significantly higher signal amplitudes and S/N ratio at 8,000 Hz. 11 The same study also reported no adverse events and no significant interference with the antitumor activity of cisplatin.…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, its use is associated with hearing loss in up to 75 to 100% of patients, leading to further worsening of their quality of life. 1 Ototoxicity results from off-target injury to the inner ear leading to cumulative and irreversible hearing loss. Its pathophysiology is thought to primarily involve oxidative damage, its major mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…RAD design workshop: this stage can be seen of as a workshop where ideas are designed and improved. Programmers and analysts can collaborate to create and convey to users visual representations of designs and workflows [16]. Depending on how big the application that has to be developed is, this design workshop may take several days to complete.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from Bank Indonesia (BI), in 2022, the amount of electronic money circulating in Indonesia was 575.3 million units, which increased by 35% in 2022 to more than 700 million units [5]. This means that many Indonesian people have started to switch to using electronic payment systems in their daily lives [6]. Indonesia is now faced with a phenomenon, namely the demographic bonus, which will reach its peak in 2045.…”
Section: Introductionmentioning
confidence: 99%